Homosexual Tradition in American Poetry. - Martin, Robert K. (University of Iowa Press, 1998)
In this expanded edition, Robert Martin sketches an account of American gay male poetry since the 1970s, including an overview of works by Rafael Campo, Mark Doty, Marlon Riggs, and Reginald Shepherd.